Three men in elaborate costumes - Sahl, Ted (photographer):::Creator::::::::::::
Group portrait of three men posing in costumes. One wears a sherrif's hat and badge; one wears a shiny, beaded outfit and cape with elaborate headdress; one wears an off the shoulder evening gown, tiara and carries a parrot on one hand.